2019
DOI: 10.1186/s12967-019-02134-9
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and computational analysis of 45 samples with a serologic weak D phenotype detected among 132,479 blood donors in northeast China

Abstract: BackgroundRH1 is one of the most clinically important blood group antigens in the field of transfusion and in the prevention of fetal incompatibility. The molecular analysis and characterization of serologic weak D phenotypes is essential to ensuring transfusion safety.MethodsBlood samples from a northeastern Chinese population were randomly screened for a serologic weak D phenotype. The nucleotide sequences of all 10 exons, adjacent flanking intronic regions, and partial 5′ and 3′ untranslated regions (UTRs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
15
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 52 publications
6
15
2
Order By: Relevance
“…RHD*DVI.3 and RHD*weak partial 15 were the most prevalent RhD variant alleles in Zhejiang province. This result was consistent with the distribution of RhD variant alleles in other regions of China ( 9 , 16 , 31 ), but it is completely different from a Caucasian population with a prevalence of less than 5% ( 32 , 35 ). There was no significant similarity or clustering in a particular site between the other rare RhD variant alleles identified in our study and those reported previously ( 3 , 9 ).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…RHD*DVI.3 and RHD*weak partial 15 were the most prevalent RhD variant alleles in Zhejiang province. This result was consistent with the distribution of RhD variant alleles in other regions of China ( 9 , 16 , 31 ), but it is completely different from a Caucasian population with a prevalence of less than 5% ( 32 , 35 ). There was no significant similarity or clustering in a particular site between the other rare RhD variant alleles identified in our study and those reported previously ( 3 , 9 ).…”
Section: Discussionsupporting
confidence: 88%
“…This result was consistent with the distribution of RhD variant alleles in To qualify as deleterious, the mutation had to be predicted as damaging by at least two of the three bioinformatics programs used. other regions of China (9,16,31), but it is completely different from a Caucasian population with a prevalence of less than 5% (32,35). There was no significant similarity or clustering in a particular site between the other rare RhD variant alleles identified in our study and those reported previously (3,9).…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…9 Several 3D bioinformatic models were proposed before the crystal structure of RhCG was resolved [17][18][19][20][21] and were based essentially on automated modeling tools. [22][23][24][25][26] These studies and others 4,27 have proposed the extracellular positions of RhD residues based almost exclusively on the prediction of the secondary structure (α helices) from the amino acid sequence, without considering the 3D conformation of the protein.…”
Section: Introductionmentioning
confidence: 99%
“…RHD*weak D type 15, RHD* DEL1, and RHD*DVI.3 are the most prevalent in the Chinese population, while other 61 RHD variants have been reported. [1][2][3] This report describes the proband and his daughter in a Chinese family with a novel allele RHD c.1228-1G>C.…”
mentioning
confidence: 99%